(untitled) (Journal of Naval Architecture and Marine Engineering, 2011)
Two-dimensional Finite Volume Method (FVM) based on Reynolds-averaged Navier-Stokes (RANS) equations is applied to solve the turbulent viscous flow around sphere and pod. Unstructured grid with boundary layer treatment is constructed around sphere whereas structured grid is generated around pod. Spalart-Allmaras (S-A) and Shear Stress Transport (SST) k-? turbulence models are used for sphere but SST k-? turbulence model is used only for pod to solve turbulent viscous flows at Reynolds number of 5×106 and 3×106 respectively. The numerical results in terms of the skin friction coefficient, pressure coefficient and drag coefficient are shown either graphically or in the tabular form. Velocity vectors as well as contour of pressure and velocity distribution are also displayed. Finally, the comparative study between flows around sphere and pod is done. DOI: http://dx.doi.org/10.3329/jname.v8i1.7388